ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS DALAM MENYELESAIKAN MASALAH OPEN ENDED BERDASARKAN GAYA BELAJAR SISWA - Nuranisa, Ai; Indrajaya, Undang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Communication skills are the transfer of mathematical ideas or concepts from one party to another. When students share their mathematical thoughts, they refer to the way or style of students in receiving. while to measure mathematical communication skills, a solution is needed so that students can develop their written communication skills, namely by providing open-ended problems so that students' mindsets are open and express their opinions by learning using an open-ended approach so that students are expected to improve their mathematical communication skills. In this study, the aim was to analyze the original mathematical communication skills in solving open-ended problems based on students' learning styles. The Open-ended approach is a learning approach that demands an open mindset, students' thinking processes do not only focus on a process or result. This type of research is qualitative descriptive research. The subjects of the study were 20 students of class VIII C of SMP Negeri 8 Garut. Data collection was carried out using a Visual, Auditory and Kinesthetic (V-A-K) learning style questionnaire, there were 6 students included in the visual learning style category, 5 students with an auditory learning style and 9 students with a kinesthetic learning style. Data collection analysis of communication skills was given an open-ended problem test taken by purposive sampling of 6 students. The results of this study indicate that there are differences in students' mathematical communication skills based on learning style categories: 1) Students with a visual style are able to illustrate pictures of problems, express ideas or solution strategies but do not provide conclusions, use mathematical symbols and notations clearly, convey reasons according to mathematical concepts. 2) Students with an auditory learning style are able to illustrate pictures of problems but do not include descriptions, express ideas for solution strategies but some are not quite right, use mathematical symbols clearly but do not make conclusions, provide reasons according to mathematical concepts. 3) Students with a kinesthetic learning style are able to illustrate pictures of problems accompanied by descriptions, express ideas for solution strategies and make conclusions, use mathematical symbols clearly, provide reasons according to mathematical concepts.